The Growth and Survival of Gouramy at Different Stocking Densities - Elvi Esa; Rusliadi Rusliadi; Iskandar Putra (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2024)
This study aims to determine the effect of different stocking densities on the growth and survival of gouramy (Osphorenemus gouramy) fed a feed containing booster aquaenzymes and to determine the best stocking density to increase growth and survival of gouramy. This research was conducted in November-January 2022 at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The container used was an aquarium with a size of 30x50x50 cm. This study used a one-factor Completely Randomized Design (CRD) method with four treatments and three replications. The treatment levels applied in this study were P1 = stocking density of 10 gourami fish/30 L, P2 = 12 fish/30 L, P3 = 14 fish/30 L and P4 = 16 fish/30 L. The results showed that there was an effect of different stocking densities on the growth and survival of gouramy. The stocking density of 10 fish/30 L gave the best growth and survival performance, namely absolute weight growth of 4.06 grams, absolute length growth of 3.25 cm, specific growth rate of 1.93%, feed efficiency 42.69% and survival rate is 96.67%. The range of water quality during maintenance is in the tolerable range for the growth of gouramy fry, namely temperatures ranging from 26.7-28.4oC, pH 6.9-7.5, DO 5.2-5.9 mg/L, and ammonia 0.00047-0.00059 mg/L.